STOMATA-A KEY FACTOR WITH MULTIPLE FUNCTIONS IN THE CONDITIONS OF GLOBAL CLIMATE CHANGE: A BRIEF OVERVIEW - Elena DELIAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The main components of climate change are carbon dioxide from the atmosphere, air temperature and drought. Considering the major changes of these parameters over time, nowadays especially, but also in the future, in order to cope properly with the new conditions, it is necessary to adjust the photosynthesis process in the sense of increasing its intensity and improving of water use efficiency. Because the stomata are formations of the epidermis involved in the process of carbon dioxide absorption (raw material in photosynthesis) and in its release (in the case of the respiration process), as well as in the release of water vapor during the transpiration, their behavior become defining for what it means not only the plants existence and their good functioning, but stomata influence is also extended and is not limited to just that. Besides the special importance for the physiological processes of plants, for plants own existence and good functioning, stomata also have significant effects for what the concentration of gases in the lower troposphere means and more than that, they can represent risks for vegetation or for human health. In view of the above, the purpose of this mini-synthesis is to present some new information on the central role played by stomata and especially their conductance property, under the conditions of climate change, in relation to the impact on plant productivity, on the carbon cycle in nature, as well as on water flow, but also on human health, with special reference to the conditions specific to the urban environment.